COMBINATION OF REVERSE OSMOSIS AND ELECTRODEIONIZATION FOR SIMULTANEOUS SUGAR RECOVERY AND SALTS REMOVAL FROM SUGARY WASTEWATER - I.N. Widiasa; I Gede Wenten (Dept. of Chemical Engineering, Diponegoro University, 2007)
An integrated membrane system combining reverse osmosis (RO) and electrodeionization (EDI) is used for simultaneous sugar concentration and salts removal from a synthetic dilute sugar solution as a model of sugar-containing wastewater. The RO system uses a thin film composite RO membrane (Saehan CSM, RE1812-60). Meanwhile, the EDI stack has two diluted compartments, one concentrated compartment, one anode compartment, and one cathode compartment. Commercially available cation exchange membrane (MC-3470) and anion exchange membrane (MA-3475) are used as ionic selective barriers of the EDI stack. Both diluate and concentrate compartments are filled with mixed ion exchange resins (purolite strong acid cation exchange, C-100E and strong base type I anion resins, A-400). Two different operation modes, i.e. RO-EDI and EDI-RO, were assessed. The experimental results show that the observed sugar rejection of RO membrane is more than 99.9% and there is no sugar loss in the EDI stack. This indicates that the hybrid process allows almost total sugar recovery. In addition, significant reduction of salts content from the concentrated sugar solution is obtained. From permeate flux and permeate purity points of view, however, the EDI-RO configuration seems superior to the RO-EDI configuration. It should be emphasized that scale formation on the membrane surface of the concentrate compartment side has to be controlled.